Oblicz wartość liczbową wyrażenia algebraicznego:
a)6x+2 dla x=2
b)7c-2d+3dla c=0,3,d=1
c)5a+3dla a=0,4
d)8r-7sdla r=7,s =0,7
e)7a-2b+9c dla a=1,b =7,c=9
f) 0,7a(do kwadratu)-1,2b(do kwadratu)-9,9c(z czwórką na górze) dla a=1,b=7,c=0
Proszę pomóżcie

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-09T13:36:52+01:00
A)6x+2 dla x=2
6*2 + 2 = 12+2 = 14

b)7c-2d+3dla c=0,3,d=1
7*0,3 -2*1 + 3 = 2,1-2+3= 3,1

c)5a+3dla a=0,4
5*0,4 + 3= 2+3 = 5

d)8r-7sdla r=7,s =0,7
8*7 - 7* 0,7 = 56 - 4,9 = 51,1

e)7a-2b+9c dla a=1,b =7,c=9
7*1-2*7+9*9 = 7-14+81 = 74

f) 0,7a(do kwadratu)-1,2b(do kwadratu)-9,9c(z czwórką na górze) dla a=1,b=7,c=0
0,7 *1²-1,2*7²-9,9*0⁴ = 0,7*1 - 1,2*49 - 9,9*0 =0,7-58,8-0= -58,1
2010-02-09T13:39:26+01:00
A) 6x + 2
6 * 2 + 2 = 12 + 2 = 14

b) 7c-2d+3
7 * 0,3 + 2 *1 = 2,1 + 2 = 4,1

c) 5a + 3
5 * 0,4 + 3 = 2 + 3 = 5

d) 8r-7s
8 * 7 - 7 * 0,7 = 56 + 4,9 = 51,1

e) 7a-2b+9c
7 * 1 - 2 * 7 + 9 * 7 = 7 - 14 + 63 = -7 + 63 = 56

f) 0,7a² - 1,2b² - 9,9c⁴
0,7 * 1² -1,2 * 7² - 9,9 * 0⁴ = 0,7 * 1 - 1,2 * 49 - 9,9 * 0 =
0,7 - 58,8 - 0 = -58,1
2010-02-09T14:08:15+01:00
A)
6x+2 =
6*2+2 =
12+2 = 14

b)
7c-2d+3 =
7*0,3-2*1+3 =
2,1-2+3 = 3,1

c)
5a+3 =
5*0,4+3 =
2+3 = 5

d)
8r-7s =
8*7-7*0,7 =
56-4,9 = 51,1

e)
7a-2b+9c =
7*1-2*7+9*9 =
7-14+81 = 74

f)
0,7a²-1,2b²-9,9c⁴ =
0,7*1²-1,2*7²-9,9*0⁴ =
0,7*1-1,2*49-9,9*0 =
0,7-58,8-0 = -58,1